Bedarfsorientiertes Kapazitätsmanagement in Supply Chains - Betz, Stefan (Ausgewählte Probleme des Logistikmanagements)

Internationale Standortwahl als strategisches Logistikproblem - Betz, Stefan (Ausgewählte Probleme des Logistikmanagements)

Dual-path source engineering in integrated quantum optics - Kruse, Regina; Sansoni, Linda; Brauner, Sebastian; Ricken, Raimund; Hamilton, Craig S.; Jex, Igor; Silberhorn, Christine (Physical Review A)

Programs from Proofs of Predicated Dataflow Analyses - Jakobs, Marie-Christine; Wehrheim, Heike (Proceedings of the 30th Annual ACM Symposium on Applied Computing)
Programs from Proofs" is a generic method which generates new programs out of correctness proofs of given programs. The technique ensures that the new and given program are behaviorally equivalent and that the new program is easily verifiable, thus serving as an alternative to proof-carrying code concepts. So far, this generic method has one instantiation that verifies type-state properties of programs. In this paper, we present a whole range of new instantiations, all based on data ow analyses. More precisely, we show how an imprecise but fast data ow analysis can be enhanced with a predicate analysis as to yield a precise but expensive analysis. Out of the safety proofs of this analysis, we generate new programs, again behaviorally equivalent to the given ones, which are easily verifiable" in the sense that now the data ow analysis alone can yield precise results. An experimental evaluation practically supports our claim of easy verification.

20 Jahre Lernen mit dem World Wide Web - Technik und Bildung im Dialog - Keil, Reinhard; Harald, Selke

Systematik zur Entwicklung einer produktlebenszyklusorientierten Geschäftsmodell-Roadmap - Peitz, Christoph

Systematik zur frühzeitigen Absicherung der Sicherheit und Zuverlässigkeit fortschrittlicher mechatronischer Systeme - Dorociak, Rafal

Augmented & Virtual Reality in der Produktentstehung: Grundlagen, Methoden und Werkzeuge; Interaktions- und Visualisierungstechniken, Virtual Prototyping intelligenter technischer Systeme mit AR/VR - Gausemeier, Jürgen; Grafe, Michael; Meyer auf der Heide, Friedhelm

Systematik zur wirtschaftlichkeitsorientierten Konzipierung Intelligenter Technischer Systeme - Vaßholz, Mareen

Verification and Simulation of Self-Adaptive Mechatronic Systems - Heinzemann, Christian

Optimizing Water Tanks in Water Distribution Systems by combining Network Reduction, Mathematical Optimization and Hydraulic Simulation - Hallmann, Corinna; Suhl, Leena (OR Spectrum)
In the last two decades, water consumption in Germany has been decreasing, which causes the water tanks and pipes in water distribution systems to work inefficiently. This paper proposes a method that supports the planning process for tanks in water distribution systems. The method uses a combination of network reduction, mathematical optimization and hydraulic simulation. The mathematical optimization model is a non-convex Mixed Integer Quadratically Constrained Program (MIQCP) that is solved by a piecewise linearization. As this may lead to many binary variables and therefore high computing times, the size of the water distribution system model is reduced before building the optimization model. After applying several network reduction techniques and using a piecewise approximation of the original model, there may be some hydraulic differences between the original network model and the reduced network model. To make sure that the solution obtained in the optimization process is feasible in the original water distribution system model, the solution is verified by a hydraulic simulation. If the solution is not feasible, the reduced model has to be modified and solved again until the hydraulic simulation verifies a solution as feasible. In this paper, each of these processes is described and the results indicate the usefulness of each of them.

Homodyne detection with on-off detector systems - Lipfert, T.; Sperling, Jan; Vogel, W. (Physical Review A)

Continuous sampling of the squeezed-state nonclassicality - Agudelo, E.; Sperling, Jan; Vogel, W.; Köhnke, S.; Mraz, M.; Hage, B. (Physical Review A)

Unified nonclassicality criteria - Ryl, S.; Sperling, Jan; Agudelo, E.; Mraz, M.; Köhnke, S.; Hage, B.; Vogel, W. (Physical Review A)

Convex ordering and quantification of quantumness - Sperling, Jan; Vogel, W (Physica Scripta)

Entanglement and phase properties of noisy NOON states - Bohmann, M.; Sperling, Jan; Vogel, W. (Physical Review A)

Entanglement witnesses for indistinguishable particles - Reusch, A.; Sperling, Jan; Vogel, W. (Physical Review A)

Nonclassicality Phase-Space Functions: More Insight with Fewer Detectors - Luis, Alfredo; Sperling, Jan; Vogel, Werner (Physical Review Letters)

Balanced homodyne detection with on-off detector systems: Observable nonclassicality criteria - Sperling, Jan; Vogel, W.; Agarwal, G. S. (EPL (Europhysics Letters))

Full Multipartite Entanglement of Frequency-Comb Gaussian States - Gerke, S.; Sperling, Jan; Vogel, W.; Cai, Y.; Roslund, J.; Treps, N.; Fabre, C. (Physical Review Letters)

Optimizing Software-Defined Networks using Application-Layer Knowledge - Wette, Philip

An overview of the BIOASQ large-scale biomedical semantic indexing and question answering competition - Tsatsaronis, George; Balikas, Georgios; Malakasiotis, Prodromos; Partalas, Ioannis; Zschunke, Matthias; R. Alvers, Michael; Weissenborn, Dirk; Krithara, Anastasia; Petridis, Sergios; Polychronopoulos, Dimitris; Almirantis, Yannis; Pavlopoulos, John; et al. (BMC Bioinform.)

Linked SDMX Data: Path to high fidelity Statistical Linked Data - Capadisli, Sarven; Auer, Sören; Ngonga Ngomo, Axel-Cyrille (Semantic Web)

Semantic Quran - Ahmed Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (Semantic Web)

SINA: Semantic interpretation of user queries for question answering on interlinked data - Shekarpour, Saeedeh; Marx, Edgard; Ngonga Ngomo, Axel-Cyrille; Auer, Sören (J. Web Semant.)

DeFacto - Temporal and multilingual Deep Fact Validation - Gerber, Daniel; Esteves, Diego; Lehmann, Jens; Bühmann, Lorenz; Usbeck, Ricardo; Ngonga Ngomo, Axel-Cyrille; Speck, René (J. Web Semant.)

Question Answering over Linked Data (QALD-5) - Unger, Christina; Forascu, Corina; López, Vanessa; Ngonga Ngomo, Axel-Cyrille; Cabrio, Elena; Cimiano, Philipp; Walter, Sebastian (Working Notes of CLEF 2015 - Conference and Labs of the Evaluation forum, Toulouse, France, September 8-11, 2015)

HAWK@QALD5 - Trying to Answer Hybrid Questions with Various Simple Ranking Techniques - Usbeck, Ricardo; Ngonga Ngomo, Axel-Cyrille (Working Notes of CLEF 2015 - Conference and Labs of the Evaluation forum, Toulouse, France, September 8-11, 2015)

CETUS - A Baseline Approach to Type Extraction - Röder, Michael; Usbeck, Ricardo; Speck, René; Ngonga Ngomo, Axel-Cyrille (Semantic Web Evaluation Challenges - Second SemWebEval Challenge at ESWC 2015, Portorož, Slovenia, May 31 - June 4, 2015, Revised Selected Papers)

Developing a Sustainable Platform for Entity Annotation Benchmarks - Röder, Michael; Usbeck, Ricardo; Ngonga Ngomo, Axel-Cyrille (Proceedings of the ESWC Developers Workshop 2015 co-located with the 12th Extended Semantic Web Conference {(ESWC} 2015), Portorož, Slovenia, May 31, 2015)

Evaluating Entity Annotators Using GERBIL - Usbeck, Ricardo; Röder, Michael; Ngonga Ngomo, Axel-Cyrille (The Semantic Web: ESWC 2015 Satellite Events - ESWC 2015 Satellite Events Portorož, Slovenia, May 31 - June 4, 2015, Revised Selected Papers)

Developing a Sustainable Platform for Entity Annotation Benchmarks - Röder, Michael; Usbeck, Ricardo; Ngonga Ngomo, Axel-Cyrille (The Semantic Web: ESWC 2015 Satellite Events - ESWC 2015 Satellite Events Portorož, Slovenia, May 31 - June 4, 2015, Revised Selected Papers)

HAWK - Hybrid Question Answering Using Linked Data - Usbeck, Ricardo; Ngonga Ngomo, Axel-Cyrille; Bühmann, Lorenz; Unger, Christina (The Semantic Web. Latest Advances and New Domains - 12th European Semantic Web Conference, ESWC 2015, Portoroz, Slovenia, May 31 - June 4, 2015. Proceedings)

Automating RDF Dataset Transformation and Enrichment - Ahmed Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille; Lehmann, Jens (The Semantic Web. Latest Advances and New Domains - 12th European Semantic Web Conference, ESWC 2015, Portoroz, Slovenia, May 31 - June 4, 2015. Proceedings)

LODFlow: a workflow management system for linked data processing - Rautenberg, Sandro; Ermilov, Ivan; Marx, Edgard; Auer, Sören; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 11th International Conference on Semantic Systems, SEMANTICS 2015, Vienna, Austria, September 15-17, 2015)

An optimization approach for load balancing in parallel link discovery - Ahmed Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 11th International Conference on Semantic Systems, SEMANTICS 2015, Vienna, Austria, September 15-17, 2015)

Motive-based Search - Avdiyenko, Liliya; Nettling, Martin; Lemke, Christiane; Wauer, Matthias; Ngonga Ngomo, Axel-Cyrille; Both, Andreas (KDIR 2015 - Proceedings of the International Conference on Knowledge Discovery and Information Retrieval, part of the 7th International Joint Conference on Knowledge Discovery, Knowledge Engineering and Knowledge Management {(IC3K} 2015), Volume 1, Lisbon, Portugal, November 12-14, 2015)

Using Caching for Local Link Discovery on Large Data Sets - M. Hassan, Mofeed; Speck, René; Ngonga Ngomo, Axel-Cyrille (Engineering the Web in the Big Data Era - 15th International Conference, ICWE 2015, Rotterdam, The Netherlands, June 23-26, 2015, Proceedings)

DeLFI 2015 - The 13th e-Learning Conference on Computer Science of the E-Learning Section of the Society for Computer Science eV - Pongratz, Hans; Keil, Reinhard

FEASIBLE: A Feature-Based SPARQL Benchmark Generation Framework - Saleem, Muhammad; Mehmood, Qaiser; Ngonga Ngomo, Axel-Cyrille (The Semantic Web - ISWC 2015 - 14th International Semantic Web Conference, Bethlehem, PA, USA, October 11-15, 2015, Proceedings, Part I)

ASSESS - Automatic Self-Assessment Using Linked Data - Bühmann, Lorenz; Usbeck, Ricardo; Ngonga Ngomo, Axel-Cyrille (The Semantic Web - ISWC 2015 - 14th International Semantic Web Conference, Bethlehem, PA, USA, October 11-15, 2015, Proceedings, Part II)

WebArena - R {\ "a} spacious structures for ü r the learning locations of the future - Winkelnkemper, Felix; Oberhoff, Andreas

An Open Question Answering Framework - Marx, Edgard; Soru, Tommaso; Esteves, Diego; Ngonga Ngomo, Axel-Cyrille; Lehmann, Jens (Proceedings of the ISWC 2015 Posters {&} Demonstrations Track co-located with the 14th International Semantic Web Conference (ISWC-2015), Bethlehem, PA, USA, October 11, 2015)

LSQ: The Linked SPARQL Queries Dataset - Saleem, Muhammad; Intizar Ali, Muhammad; Hogan, Aidan; Mehmood, Qaiser; Ngonga Ngomo, Axel-Cyrille (The Semantic Web - ISWC 2015 - 14th International Semantic Web Conference, Bethlehem, PA, USA, October 11-15, 2015, Proceedings, Part II)

The LSQ Dataset: Querying for Queries - Saleem, Muhammad; Intizar Ali, Muhammad; Hogan, Aidan; Mehmood, Qaiser; Ngonga Ngomo, Axel-Cyrille (Proceedings of the ISWC 2015 Posters {&} Demonstrations Track co-located with the 14th International Semantic Web Conference (ISWC-2015), Bethlehem, PA, USA, October 11, 2015)

Automatic SPARQL Benchmark Generation using FEASIBLE - Saleem, Muhammad; Mehmood, Qaiser; Ngonga Ngomo, Axel-Cyrille (Proceedings of the ISWC 2015 Posters {&} Demonstrations Track co-located with the 14th International Semantic Web Conference (ISWC-2015), Bethlehem, PA, USA, October 11, 2015)

LANCE: Piercing to the Heart of Instance Matching Tools - Saveta, Tzanina; Daskalaki, Evangelia; Flouris, Giorgos; Fundulaki, Irini; Herschel, Melanie; Ngonga Ngomo, Axel-Cyrille (The Semantic Web - ISWC 2015 - 14th International Semantic Web Conference, Bethlehem, PA, USA, October 11-15, 2015, Proceedings, Part I)

LANCE: A Generic Benchmark Generator for Linked Data - Saveta, Tzanina; Daskalaki, Evangelia; Flouris, Giorgos; Fundulaki, Irini; Ngonga Ngomo, Axel-Cyrille (Proceedings of the ISWC 2015 Posters {&} Demonstrations Track co-located with the 14th International Semantic Web Conference (ISWC-2015), Bethlehem, PA, USA, October 11, 2015)

Enhancing Dataset Quality using Keys - Soru, Tommaso; Marx, Edgard; Ngonga Ngomo, Axel-Cyrille (Proceedings of the ISWC 2015 Posters {&} Demonstrations Track co-located with the 14th International Semantic Web Conference (ISWC-2015), Bethlehem, PA, USA, October 11, 2015)

Interlinking: Performance Assessment of User Evaluation vs. Supervised Learning Approaches - M. Hassan, Mofeed; Lehmann, Jens; Ngonga Ngomo, Axel-Cyrille (Proceedings of the Workshop on Linked Data on the Web, LDOW 2015, co-located with the 24th International World Wide Web Conference {(WWW} 2015), Florence, Italy, May 19th, 2015)

Pushing the Limits of Instance Matching Systems: A Semantics-Aware Benchmark for Linked Data - Saveta, Tzanina; Daskalaki, Evangelia; Flouris, Giorgos; Fundulaki, Irini; Herschel, Melanie; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 24th International Conference on World Wide Web Companion, WWW 2015, Florence, Italy, May 18-22, 2015 - Companion Volume)

CubeViz: Exploration and Visualization of Statistical Linked Data - Martin, Michael; Abicht, Konrad; Stadler, Claus; Ngonga Ngomo, Axel-Cyrille; Soru, Tommaso; Auer, Sören (Proceedings of the 24th International Conference on World Wide Web Companion, WWW 2015, Florence, Italy, May 18-22, 2015 - Companion Volume)

ROCKER: A Refinement Operator for Key Discovery - Soru, Tommaso; Marx, Edgard; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 24th International Conference on World Wide Web, WWW 2015, Florence, Italy, May 18-22, 2015)

GERBIL: General Entity Annotator Benchmarking Framework - Usbeck, Ricardo; Röder, Michael; Ngonga Ngomo, Axel-Cyrille; Baron, Ciro; Both, Andreas; Brümmer, Martin; Ceccarelli, Diego; Cornolti, Marco; Cherix, Didier; Eickmann, Bernd; Ferragina, Paolo; Lemke, Christiane; et al. (Proceedings of the 24th International Conference on World Wide Web, WWW 2015, Florence, Italy, May 18-22, 2015)

Managing Geospatial Linked Data in the GeoKnow Project - Lehmann, Jens; Athanasiou, Spiros; Both, Andreas; García-Rojas, Alejandra; Giannopoulos, Giorgos; Hladky, Daniel; Jay Le Grange, Jon; Ngonga Ngomo, Axel-Cyrille; Ahmed Sherif, Mohamed; Stadler, Claus; Wauer, Matthias; Westphal, Patrick; et al. (The Semantic Web in Earth and Space Science. Current Status and Future Directions)

Microwave Experiments Simulating Quantum Search and Directed Transport in Artificial Graphene - Böhm, Julian; Bellec, Matthieu; Mortessagne, Fabrice; Kuhl, Ulrich; Barkhofen, Sonja; Gehler, Stefan; Stöckmann, Hans-Jürgen; Foulger, Iain; Gnutzmann, Sven; Tanner, Gregor (Physical Review Letters)

Compounding approach for univariate time series with nonstationary variances - Schäfer, Rudi; Barkhofen, Sonja; Guhr, Thomas; Stöckmann, Hans-Jürgen; Kuhl, Ulrich (Physical Review E)

Optimierung von Wasserbehältern in einem Wasserversorgungssystem mittels einer Kombination aus Netzreduktion, mathematischer Optimierung und hydraulischer Simulation - Hallmann, Corinna

Quantum walk coherences on a dynamical percolation graph - Elster, Fabian; Barkhofen, Sonja; Nitsche, Thomas; Novotný, Jaroslav; Gábris, Aurél; Jex, Igor; Silberhorn, Christine (Scientific Reports)

20 years of learning with the World Wide Web - technology and education in dialogue

Learn with, through and {\ "about the WWW - Keil, Reinhard; Selke, Harald

Virtual knowledge {\ "a} ume - From the presentation of content to virtual learning ä tten - Keil, Reinhard; Selke, Harald

Development of a structured process of interaction design for {\ "u} r nat ü local user interfaces - Klompmaker, Florian

Empirical validation of design patterns - Schild, Christian; Petrausch, Vanessa (Human and Computer 2015 - Proceedings)
Patterns serve to codify design knowledge. By embedding them in a hypothesis-driven design, it is possible to develop them further into sample languages. For this it is necessary to resolve the underlying conflicts in the form of design hypotheses and to validate them empirically in order to enable further use and generalization. In this article, an experiment is presented that describes this procedure and demonstrates the interplay between theory formation and codification of design knowledge using two examples.

Online Resource Leasing - Markarian, Christine; Meyer auf der Heide, Friedhelm (Proceedings of the 2015 ACM Symposium on Principles of Distributed Computing (PODC))
Many markets have seen a shift from the idea of buying and moved to leasing instead. Arguably, the latter has been the major catalyst for their success. Ten years ago, research realized this shift and initiated the study of "online leasing problems" by introducing leasing to online optimization problems. Resources required to provide a service in an "online leasing problem" are no more bought but leased for different durations. In this paper, we provide an overview of results that contribute to the understanding of "online resource leasing problems".

Einstellungen von Grundschullehrkräften zum inklusiven Lernen in Abhängigkeit von dem Umfang an Erfahrungen aus dem Unterricht mit Kindern mit unterschiedlichen sonderpädagogischen Förderbedarfen - Hellmich, Frank; Görel, Gamze (Veränderung und Beständigkeit in Zeiten der Inklusion. Perspektiven sonderpädagogischer Professionalisierung)

Online Resource Leasing - Markarian, Christine

Entwicklung naturwissenschaftlich-technischer Lehr-Lernangebote für inklusiven Sachunterricht - Blumberg, Eva; Hellmich, Frank; Fromme, Theresa (Lernprozessbegleitung und adaptives Lernen in der Grundschule. Forschungsbezogene Beiträge)

Kausalattributionen von Leseerfolgen und Lesemisserfolgen bei Kindern im Leseunterricht der Grundschule - Ort, Margarita; Hellmich, Frank (Facetten grundschulpädagogischer und -didaktischer Forschung)

Lesestrategien und Leseerfolg bei Kindern im vierten Grundschuljahr – Analysen mit Fragebogen- und Beobachtungsverfahren - Hellmich, Frank (Innovative Erhebungsmethoden – dargestellt an verschiedenen Forschungsprojekten)

Online Bewertungssysteme – Ein systematischer Überblick - Lange, Alexander

Gesellschaftliche und kulturelle Bedeutung von Mittagsverpflegung in Gießener Kindertagesstätten - Klünder, Nina (Hauswirtschaft und Wissenschaft)

Verpflegung in Kindertagesstätten gestalten – Ergebnisse einer qualitativen Studie - Meier-Gräwe, Uta; Klünder, Nina (KiTa aktuell)

On-The-Fly Verification of Reconfigurable Image Processing Modules based on a Proof-Carrying Hardware Approach - Wiersema, Tobias; Wu, Sen; Platzner, Marco (Proceedings of the International Symposium in Reconfigurable Computing (ARC))
Proof-carrying hardware is an approach that has recently been proposed for the efficient verification of reconfigurable modules. We present an application of proof-carrying hardware to guarantee the correct functionality of dynamically reconfigured image processing modules. Our prototype comprises a reconfigurable-system-on-chip with an embedded virtual FPGA fabric. This setup allows us to leverage open source FPGA synthesis and backend tools to produce FPGA configuration bitstreams with an open format and, thus, to demonstrate and experimentally evaluate proof-carrying hardware at the bitstream level.

Effects of human milk and formula on postprandial glycaemia and insulinaemia - Wright, C J; Atkinson, F S; Ramalingam, N; Buyken, Anette; Brand-Miller, J C (European Journal of Clinical Nutrition)

Dietary micronutrient intake during pregnancy is a function of carbohydrate quality - Goletzke, Janina; Buyken, Anette; Louie, Jimmy CY; Moses, Robert G; Brand-Miller, Jennie C (The American Journal of Clinical Nutrition)

Early Diet and Later Cancer Risk: Prospective Associations of Dietary Patterns During Critical Periods of Childhood with the GH-IGF Axis, Insulin Resistance and Body Fatness in Younger Adulthood - Günther, Anke L. B.; Schulze, Matthias B.; Kroke, Anja; Diethelm, Katharina; Joslowski, Gesa; Krupp, Danika; Wudy, Stefan; Buyken, Anette (Nutrition and Cancer)

Relevance of fruits, vegetables and flavonoids from fruits and vegetables during early life, mid-childhood and adolescence for levels of insulin-like growth factor (IGF-1) and its binding proteins IGFBP-2 and IGFBP-3 in young adulthood - Krupp, Danika; Remer, Thomas; Penczynski, Katharina J.; Bolzenius, Katja; Wudy, Stefan A.; Buyken, Anette (British Journal of Nutrition)
Abstract The growth hormone (GH) insulin-like growth factor (IGF) axis has been linked to insulin metabolism and cancer risk. Experimental evidence indicates that the GH–IGF axis itself can be influenced by dietary flavonoids. As fruit and vegetable (FV) intake is a major source of flavonoid consumption, FV’s beneficial health effects may be explained via flavonoids’ influence on the GH–IGF axis, but observational evidence is currently rare. We used data from Dortmund Nutritional and Anthropometric Longitudinally Designed Study participants to analyse prospective associations between FV, fruit intake and flavonoid intake from FV (FlavFV) with IGF-1 and its binding proteins IGFBP-2 and IGFBP-3. Subjects needed to provide a fasting blood sample in adulthood (18–39 years) and at least two 3-d weighed dietary records in early life (0·5−2 years, n 191), mid-childhood (3−7 years, n 265) or adolescence (girls: 9−15 years, boys: 10−16 years, n 261). Additional analyses were conducted among those providing at least three 24-h urine samples in adolescence ( n 236) to address the predictor urinary hippuric acid (HA), a biomarker of polyphenol intake. Higher fruit intake in mid-childhood and adolescence was related to higher IGFBP-2 in adulthood ( P =0·03 and P =0·045). Comparable trends ( P =0·045−0·09) were discernable for FV intake (but not FlavFV) in all three time windows. Similarly, higher adolescent HA excretion tended to be related ( P =0·06) to higher adult IGFBP-2 levels. Regarding IGFBP-3, a marginal ( P =0·08) positive association was observed with FlavFV in mid-childhood only. None of the investigated dietary factors was related to IGF-1. In conclusion, higher fruit and FV intakes during growth may be relevant for adult IGFBP-2, but probably not for IGFBP-3 or IGF-1.

Relative validation of 24-h urinary hippuric acid excretion as a biomarker for dietary flavonoid intake from fruit and vegetables in healthy adolescents - Penczynski, Katharina J.; Krupp, Danika; Bring, Anna; Bolzenius, Katja; Remer, Thomas; Buyken, Anette (European Journal of Nutrition)

Approximate Pure Nash Equilibria in Weighted Congestion Games: Existence, Efficient Computation, and Structure - Caragiannis, Ioannis; Fanelli, Angelo; Gravin, Nick; Skopalik, Alexander (Transactions on Economics and Computation)
We consider structural and algorithmic questions related to the Nash dynamics of weighted congestion games. In weighted congestion games with linear latency functions, the existence of pure Nash equilibria is guaranteed by a potential function argument. Unfortunately, this proof of existence is inefficient and computing pure Nash equilibria in such games is a PLS-hard problem even when all players have unit weights. The situation gets worse when superlinear (e.g., quadratic) latency functions come into play; in this case, the Nash dynamics of the game may contain cycles and pure Nash equilibria may not even exist. Given these obstacles, we consider approximate pure Nash equilibria as alternative solution concepts. A ρ--approximate pure Nash equilibrium is a state of a (weighted congestion) game from which no player has any incentive to deviate in order to improve her cost by a multiplicative factor higher than ρ. Do such equilibria exist for small values of ρ? And if so, can we compute them efficiently?We provide positive answers to both questions for weighted congestion games with polynomial latency functions by exploiting an “approximation” of such games by a new class of potential games that we call Ψ-games. This allows us to show that these games have d!-approximate pure Nash equilibria, where d is the maximum degree of the latency functions. Our main technical contribution is an efficient algorithm for computing O(1)-approximate pure Nash equilibria when d is a constant. For games with linear latency functions, the approximation guarantee is 3+√5/2 + Oγ for arbitrarily small γ > 0; for latency functions with maximum degree d≥ 2, it is d2d+o(d). The running time is polynomial in the number of bits in the representation of the game and 1/γ. As a byproduct of our techniques, we also show the following interesting structural statement for weighted congestion games with polynomial latency functions of maximum degree d ≥ 2: polynomially-long sequences of best-response moves from any initial state to a dO(d2)-approximate pure Nash equilibrium exist and can be efficiently identified in such games as long as d is a constant.To the best of our knowledge, these are the first positive algorithmic results for approximate pure Nash equilibria in weighted congestion games. Our techniques significantly extend our recent work on unweighted congestion games through the use of Ψ-games. The concept of approximating nonpotential games by potential ones is interesting in itself and might have further applications.

Anonymous credential system based on q-Strong Diffie-Hellman Assumption - Eidens, Fabian

Anonymous and Publicly Linkable Reputation Systems - Blömer, Johannes; Juhnke, Jakob; Kolb, Christina (Proceedings of the 18th International Conference on Financial Cryptography and Data Security (FC))
Reputation systems are used to compute and publish reputation scores for services or products. We consider reputation systems where users are allowed to rate products that they purchased previously. To obtain trustworthy reputations, they are allowed to rate these products only once. As long as users rate products once, they stay anonymous. Everybody is able to detect users deviating from the rate-products-only-once policy and the anonymity of such dishonest users can be revoked by a system manager. In this paper we present formal models for such reputation systems and their security. Based on group signatures presented by Boneh, Boyen, and Shacham we design an efficient reputation system that meets all our requirements.

An approach towards adaptive service composition in markets of composed services - Jungmann, Alexander; Mohr, Felix (Journal of Internet Services and Applications)
On-the-fly composition of service-based software solutions is still a challenging task. Even more challenges emerge when facing automatic service composition in markets of composed services for end users. In this paper, we focus on the functional discrepancy between “what a user wants” specified in terms of a request and “what a user gets” when executing a composed service. To meet the challenge of functional discrepancy, we propose the combination of existing symbolic composition approaches with machine learning techniques. We developed a learning recommendation system that expands the capabilities of existing composition algorithms to facilitate adaptivity and consequently reduces functional discrepancy. As a representative of symbolic techniques, an Artificial Intelligence planning based approach produces solutions that are correct with respect to formal specifications. Our learning recommendation system supports the symbolic approach in decision-making. Reinforcement Learning techniques enable the recommendation system to adjust its recommendation strategy over time based on user ratings. We implemented the proposed functionality in terms of a prototypical composition framework. Preliminary results from experiments conducted in the image processing domain illustrate the benefit of combining both complementary techniques.

A Metric for Functional Reusability of Services - Mohr, Felix (Proceedings of the 14th International Conference on Software Reuse (ICSR))
Services are self-contained software components that can beused platform independent and that aim at maximizing software reuse. Abasic concern in service oriented architectures is to measure the reusabilityof services. One of the most important qualities is the functionalreusability, which indicates how relevant the task is that a service solves.Current metrics for functional reusability of software, however, have verylittle explanatory power and do not accomplish this goal.This paper presents a new approach to estimate the functional reusabilityof services based on their relevance. To this end, it denes the degreeto which a service enables the execution of other services as its contri-bution. Based on the contribution, relevance of services is dened as anestimation for their functional reusability. Explanatory power is obtainedby normalizing relevance values with a reference service. The applicationof the metric to a service test set conrms its supposed capabilities.

A Group Signature Scheme with Distributed Group Management - An Application of Threshold Encryption - Löken, Nils

A group signature scheme based on the LSRW assumption - Heihoff, Frederic

A deterministic worst-case message complexity optimal solution for resource discovery - Kniesburges, Sebastian; Koutsopoulos, Andreas; Scheideler, Christian (Theoretical Computer Science)
We consider the problem of resource discovery in distributed systems. In particular we give an algorithm, such that each node in a network discovers the address of any other node in the network. We model the knowledge of the nodes as a virtual overlay network given by a directed graph such that complete knowledge of all nodes corresponds to a complete graph in the overlay network. Although there are several solutions for resource discovery, our solution is the first that achieves worst-case optimal work for each node, i.e. the number of addresses (O(n)O(n)) or bits (O(nlog⁡n)O(nlog⁡n)) a node receives or sends coincides with the lower bound, while ensuring only a linear runtime (O(n)O(n)) on the number of rounds.

Will They Die Another Day? A Decision Support Perspective on Reusing Electric Vehicle Batteries - Beverungen, Daniel; Klör, Benjamin; Bräuer, Sebastian; Monhof, Markus (Proceedings of the Twenty-Third European Conference on Information Systems (ECIS 2015))

A Market for Trading Used Electric Vehicle Batteries — Theoretical Foundations and Information Systems - Klör, Benjamin; Beverungen, Daniel; Bräuer, Sebastian; Plenter, Florian; Monhof, Markus (Proceedings of the Twenty-Third European Conference on Information Systems (ECIS 2015))

Sustaining Civil Peace: a configurational comparative analysis - Gries, Thomas; Palnau, Irene (Peace Economics, Peace Science and Public Policy)

Oppressive Governments, Dependence on the United States and Anti-American Terrorism - Gries, Thomas; Meierrieks, Daniel; Redlin, Margarete (Oxford Economic Papers)

Erfolg durch Persönlichkeit? Der Einfluss der Markenpersönlichkeit auf den Zusammenhang von Reputation und Unternehmenserfolg - Fanasch, Patrizia

Die Veränderung des Mobilfunkmarktes durch die Discountanbieter - Walczok, Gregor Paul

Learning Boolean Specifications - Bubeck, Uwe; Kleine Büning, Hans (Artificial Intelligence)
In this paper we consider an extended variant of query learning where the hidden concept is embedded in some Boolean circuit. This additional processing layer modifies query arguments and answers by fixed transformation functions which are known to the learner. For this scenario, we provide a characterization of the solution space and an ordering on it. We give a compact representation of the minimal and maximal solutions as quantified Boolean formulas and we adapt the original algorithms for exact learning of specific classes of propositional formulas.
Keywords: Query learning; Propositional logic

Evaluation von Bildverarbeitungsalgorithmen in heterogenen Rechenknoten - Knorr, Christoph

A Domain-Specific Modeling Language for Electric Vehicle Batteries - Klör, Benjamin; Bräuer, Sebastian; Beverungen, Daniel; Monhof, Markus (Proceedings of the 12. International Conference on Wirtschaftsinformatik 2015 (WI 2015))

Extending Battery Management Systems for Making Informed Decisions on Battery Reuse - Monhof, Markus; Beverungen, Daniel; Klör, Benjamin; Bräuer, Sebastian (New Horizons in Design Science: Broadening the Research Agenda)

Neue Bildungslandschaften - Kommunales Bildungsmanagement als Zukunftsaufgabe - Euler, Dieter; Sloane, Peter F. E. (Zeitschrift für Berufs-und Wirtschaftspädagogik)

Die Bedeutung subjektiver Sichtweisen für die Implementierung betrieblicher Lernkultur - Fischer, Christoph; Harteis, Christian (Informelles Lernen, Annäherungen - Problemlagen - Forschungsbefunde)
Keywords: Epistemische Überzeugungen; learning culture

Effects of age, gender and occupation on perceived workplace learning support - Harteis, Christian; Billett, Stephen; Goller, Michael; Rausch, Andreas; Seifried, J{\ (International journal of training research)